SINTESIS LOGAM BESI (Fe) BERBASIS AIR KOLONG MENGGUNAKAN METODE ELEKTROKOAGULASI - Miratsi, Lizia; Yulinda, Yulinda; Junaidi, Junaidi; Kurniawan, Widodo Budi (Prodi Fisika FST UNJA, 2024)
After a land is excavated for tin mining purposes, a hole called a kolong will be formed. Kolong has the potential to be a new water resource, but the condition of kolong water still contains dangerous metals, one of which is iron (Fe) and kolong water does not meet the standard requirements for clean water quality. Therefore, this research aims to reduce concentration of iron (Fe) and synthesizing Fe metal contained in kolong using the electrocoagulation method. This method is environmentally friendly and effective for application in kolong areas, besides that it is easy to separate pollutants because coagulated sediments called floc float on the surface. The electrocoagulation method is applied using an aluminum plate with variations in electrocoagulation time. Based on the AAS test results, it shows that there is a decrease in Fe levels in kolong water after electrocoagulation. The results of the XRF and Thus, using the electrocoagulation method can reduce levels of iron metal (Fe) and synthesize Fe metal in kolong water.